(untitled) (Human Factors in Design, 2021)
This paper aims to identify and analyze how the sighted user and the visually impaired user interact with the washing machine in order to identify its accessibility, usability and user experience. For this purpose, an exploratory study was carried out with sighted and blind people, which consists of a task analysis of washing clothes, associated with pre- and post-questionnaires to identify the ease of starting the product, the satisfaction in using it, and its level of accessibility. The results show that the highest difficulties found during the task of washing clothes are related to activities of separating clothes, selecting the appropriate washing program, and inserting soap and softener in the corresponding compartments.